CHATGPT DAN ARTIFICIAL INTELLIGENCE: KEKACAUAN ATAU KEBANGUNAN BAGI PENDIDIKAN AGAMA KRISTEN DI ERA POSTMODERN - Frans Pantan (Diegesis : Jurnal Teologi, 2023)
Artificial intelligence is increasingly used in various fields and disciplines. The discourse always associated with its use is the efficiency and speed produced. One of the Artificial intelligence developments is ChatGPT, a platform to get answers to theoretical questions. The presence of ChatGPT gave birth to pros and cons among Christian religious educators. This research aims to study the idea of ChatGPT in Christian Religious Education. The method used is qualitative with a netnography approach. The research results show that ChatGPT will reduce the values in Christian Religious Education as a learning process to become like Jesus. Nevertheless, on the other hand, ChatGPT can be used as a broad overview of something.